Exploratory Clinical Study on Controlled álak Microdosing for Post-Detoxification Recovery - Roland Mario; Festin Bermudez; Mary Fresthel; Dominic Calingasan Agoncillo; Jamora Santos; Ann Monica Espaldon (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Post-detoxification phases of methamphetamine dependence are often characterized by neurophysiological instability, including tremors, insomnia, and anxiety, due to suppressed GABAergic activity and hyperdopaminergic rebound. Traditional Filipino distilled spirit, álak or lambanog, contains trace levels of ethanol and minor fusel alcohols which may exert mild GABA-A receptor agonism when microdosed under medical supervision. This exploratory clinical study investigates the potential of controlled álak microdosing as an adjunct for stabilizing central nervous system function in post-detoxified methamphetamine patients. Twelve post-detoxification patients (n=12) from rehabilitation centers in Quezon and Batangas were administered álak microdoses (≤10% ethanol, 5–10 ml/day) for 14 days under medical supervision. Physiological and psychological parameters including sleep quality, tremor frequency, and anxiety, were measured using the Clinical Opiate Withdrawal Scale (COWS) adapted for stimulant recovery and the Beck Anxiety Inventory (BAI). Data were analyzed descriptively and statistically using paired t-tests. Eight out of twelve participants (66.7%) demonstrated marked improvement in sleep continuity (p<0.05), tremor reduction (p<0.05), and decreased anxiety scores (mean reduction 23.4%, p<0.05). No signs of ethanol intoxication, craving substitution, or hepatic distress were observed. Mild headache was reported in one participant but resolved spontaneously. Controlled álak microdosing exhibits promising GABAergic modulatory effects that may facilitate neurophysiological stabilization in methamphetamine recovery. While preliminary, these findings support further biochemical validation and integration of ethnopharmacological knowledge into harm-reduction frameworks.